PENGARUH MODEL PEMBELAJARAN DRTA BERBANTUAN MEDIA KOMIK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SEKOLAH DASAR - Alvista, Alvista Merry Tania; Yuni Purwanti, Kartika (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the effect of the Direct Reading Thinking Activity (DRTA) learning model assisted by comics on the reading comprehension ability of fourth grade students at SDN Genuk Ungaran Barat. This study uses a quantitative approach with an experimental method, namely Quasi Experimental Design in the form of a Non-Equivalent Control Group Design. The population in this study were all fourth grade students at SDN Genuk Ungaran Barat. Meanwhile, the samples in this study were fourth grade students at SDN Genuk 01 and fourth grade students at SDN Genuk 02 Ungaran Barat. Data collection techniques used cognitive domain tests, observations, interviews and documentation. The data analysis technique used is the Independent Sample T-Test and Simple Linear Regression Test. The results of this study indicate: (1) There is an average difference in students' reading comprehension skills between the control class and the experimental class, which can be seen from the Independent Sample T-Test and the tcount > ttable (3,611 > 2,008) with a sig. (2-tailed) that is 0.001 < 0.05 then H0 is rejected and Ha is accepted. (2) There is an influence of the Direct Reading Thinking Activity (DRTA) learning model assisted by comics media on students' reading comprehension skills, which can be seen from the Simple Linear Regression Test and obtained a significance level of 0.000 < 0.05 with a percentage value of R2 = 0.573 = 57 ,3%, then this regression model can affect the participation variable. So it can be concluded that the Direct Reading Thinking Activity (DRTA) learning model assisted by comics media affects the reading comprehension ability of fourth grade students at SDN Genuk Ungaran Barat. Keywords: DRTA Learning Model; Comic Media; Reading Comprehension Ability.